Dynamic Covalent Bond-Based Nanoassembly of Curcumin to Enhance the Selective Photothermal Therapy for Tumor Treatment [Corrigendum] - Qin J; Fan G; Lv Y; Zhang J; Geng S; Ma L; Wang L; Yang J; Zhang W; Zhan Y; Wang X; Ma J (International Journal of Nanomedicine)
Qin J, Fan G, Lv Y, et al. Int J Nanomedicine. 2025;20:3861—3875. The authors have advised there is an error in Scheme 1 on page 3863. Specifically, a boron atom was incorrectly depicted as a nitrogen atom. The correct Scheme 1 is shown below.